2011
DOI: 10.1080/17445302.2010.514716
|View full text |Cite
|
Sign up to set email alerts
|

Crew noise exposure on board ships and comparative study of applicable standards

Abstract: In recent years, transport activities have radically increased due to globalisation, growth in wealth and freedom of movement. The shipping industry has responded to increased needs by providing flexible operations using new types of ships, equipped with novel technologies, materials and propulsion systems. Furthermore, services have been extended to new geographical areas including locations in and around populated cities. Naturally such services, in addition to the benefits, create various types of problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 5 publications
1
13
0
2
Order By: Relevance
“…As exposure to loud noises, such as in engine rooms, is unavoidable on fishing boats, hearing protection within these areas is mandatory. Devices for hearing protection including earplugs or earmuffs can be easily sourced and used on board [49]. Neitzel et al showed that the use of hearing protector devices during working activities reduced the average exposure by about 10 dBA, but not all workers wore them consistently due to communication demands [50].…”
Section: Discussionmentioning
confidence: 99%
“…As exposure to loud noises, such as in engine rooms, is unavoidable on fishing boats, hearing protection within these areas is mandatory. Devices for hearing protection including earplugs or earmuffs can be easily sourced and used on board [49]. Neitzel et al showed that the use of hearing protector devices during working activities reduced the average exposure by about 10 dBA, but not all workers wore them consistently due to communication demands [50].…”
Section: Discussionmentioning
confidence: 99%
“…The study involved a number of technicians and researchers from 14 European institutions in 9 countries and constitutes a noticeable landmark for this subject, since different aspects and possible progress have been analysed in details. SILENV general output can be found at the project website (SILENV, 2012a), while more specific results are reported by Turan et al (2011) and Badino et al (2012b). Noise measurements carried out on-board six chemicals tankers are presented and examined by Turan et al (2011) within the context of the IMO Resolution A.468 (XII) (IMO, 1981) and of the EU Directive 2003/ 10/EC (EU, 2003) as well.…”
Section: Review Of the Available Literaturementioning
confidence: 99%
“…SILENV general output can be found at the project website (SILENV, 2012a), while more specific results are reported by Turan et al (2011) and Badino et al (2012b). Noise measurements carried out on-board six chemicals tankers are presented and examined by Turan et al (2011) within the context of the IMO Resolution A.468 (XII) (IMO, 1981) and of the EU Directive 2003/ 10/EC (EU, 2003) as well. After discussing the basic aspects of noise exposure, the paper investigates the difference between the EU and IMO standards and their effect on crew.…”
Section: Review Of the Available Literaturementioning
confidence: 99%
“…The noise generated by the propeller has a significant contribution to the total noise of the ship. In addition to the environmental impacts, the noise of ships can affect the health and comfort of the crew and passengers of the ship [1,2]. For warships, high levels of noise may cause detection and possible dangers for the ship.…”
Section: Introductionmentioning
confidence: 99%